2016
DOI: 10.1158/2326-6066.cir-14-0176
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Autoantibodies Are Not Elevated in Lung Cancer When Assayed Controlling for Specificity and Smoking Status

Abstract: The high mortality rate in lung cancer is largely attributable to late diagnosis. Case-control studies suggest that autoantibodies to the survivin protein are potential biomarkers for early diagnosis. We tested the hypothesis that sandwich ELISA can detect autoantibodies to survivin before radiologic diagnosis in patients with early-stage non-small cell lung cancer (NSCLC). Because previous studies assayed survivin autoantibodies with the direct antigencoating ELISA (DAC-ELISA), we first compared that assay wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A recent report by the National Cancer Center, China, indicated that lung cancer was also the first cause of cancer death in China; in 2013, about 733 000 cases were newly diagnosed with lung cancer and about 591 000 cases that died of lung cancer [4]. Nonsmall cell lung cancer (NSCLC) is the most common type of lung cancer, accounting for 80-85% of all cases with this malignancy [5].The high mortality rate of lung cancer is largely attributable to late diagnosis [6]. If this malignant tumor was identified at stage 1, the 5-year survival rate can rise from less than 15% on average to 50% [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report by the National Cancer Center, China, indicated that lung cancer was also the first cause of cancer death in China; in 2013, about 733 000 cases were newly diagnosed with lung cancer and about 591 000 cases that died of lung cancer [4]. Nonsmall cell lung cancer (NSCLC) is the most common type of lung cancer, accounting for 80-85% of all cases with this malignancy [5].The high mortality rate of lung cancer is largely attributable to late diagnosis [6]. If this malignant tumor was identified at stage 1, the 5-year survival rate can rise from less than 15% on average to 50% [7].…”
mentioning
confidence: 99%
“…The high mortality rate of lung cancer is largely attributable to late diagnosis [6]. If this malignant tumor was identified at stage 1, the 5-year survival rate can rise from less than 15% on average to 50% [7].…”
mentioning
confidence: 99%
“…The autoantibody repertoire of patients who were administrated treatment has been shown to differ from the autoantibody repertoire of newly diagnosed patients (17); hence, it seemed good if the data on the treatments administrated for these patients (treatment history) were added. Smoking, as the major risk factor for lung cancer, has been considered in different studies (3,9,18). However, this study lacked any data regarding whether the patients and healthy individuals (as controls) were smokers or non-smokers.…”
Section: Editorialmentioning
confidence: 99%
“…Four TAAs, including cyclin B1, HCC1, p53, and survivin, were used in this study to evaluate their potential as cancer biomarkers. As the authors pointed out, the roles of these TAAs in lung cancer have been demonstrated in many studies (9,10,(16)(17)(18)(20)(21)(22)(23)(24)(25)(26). Because the diagnostic value of a single marker is relatively low, different combinations of these antigens were also used to simultaneously detect antibodies associated with lung cancer (9,10,20,21,26).…”
Section: Editorialmentioning
confidence: 99%
“…Other types include lung adenocarcinoma (LUAD), lung squamous cell carcinoma (LUSC) and large cell carcinoma ( 5 ). Due to the nonspecific symptoms at early stages and poor overall survival rates ( 6 , 7 ), association studies for NSCLC biomarkers have been investigated globally ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%